The Influence of Tax Awareness, Tax Knowledge, and Tax Socialization of Value Added Tax Imposition on Tax Compliance of E-Commerce Users - Toly, Agus Arianto; Sandova, Grace Alicia; Hutabarat, Meity Sestiana Sylvie (Journal of International Conference Proceedings, 2023)
The importance of tax compliance is a crucial element in optimizing tax revenues. Taxpayers (WP) who do not comply can result in a decrease in tax revenue. Tax compliance includes complying with tax regulations and disclosing income accurately and honestly. This research aims to find out how socialization, awareness, and knowledge of taxation influence taxpayer compliance in Indonesia, especially among business actors who have online shops on Shopee E-Commerce. A quantitative approach was used in this research. Questionnaires were distributed throughout the Gerbangkertosusila area (Gresik, Bangkalan, Mojokerto, Surabaya, Sidoarjo, and Lamongan) to collect data. After getting the data, the data was processed using SPSS version 20 with linear regression. The research findings are as follows: (1) tax compliance among e-commerce users is significantly influenced by tax knowledge, (2) e-commerce consumer compliance with tax regulations is influenced by tax awareness, and (3) tax socialization influences on compliance with e-commerce consumer tax. This research advises the government and related institutions to intensify the provision of information and increase tax outreach efforts among e-commerce business actors. Keywords: Tax Compliance, Value Added Tax, E-Commerce